2013
DOI: 10.1089/jpm.2013.0276
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Use for Symptom Management in Patients Receiving Hospice and Palliative Care: A Systematic Review

Abstract: Background: Patients receiving hospice or palliative care often receive antimicrobial therapy; however the effectiveness of antimicrobial therapy for symptom management in these patients is unknown. Objective: The study's objective was to systematically review and summarize existing data on the prevalence and effectiveness of antimicrobial therapy to improve symptom burden among hospice or palliative care patients. Design: Systematic review of articles on microbial use in hospice and palliative care patients p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 17 publications
1
79
0
10
Order By: Relevance
“…Other studies have reported a prevalence of antibiotic use exceeding 50% with higher prevalence estimates occurring in dedicated palliative care units within hospitals where patients are receiving entirely or primarily supportive care. [14] In the study by Reinbolt et al described above, 92% (633/685) of diagnosed infections were treated with antimicrobial therapy. [13] …”
Section: Infection and Antibiotic Use In Hospice Carementioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have reported a prevalence of antibiotic use exceeding 50% with higher prevalence estimates occurring in dedicated palliative care units within hospitals where patients are receiving entirely or primarily supportive care. [14] In the study by Reinbolt et al described above, 92% (633/685) of diagnosed infections were treated with antimicrobial therapy. [13] …”
Section: Infection and Antibiotic Use In Hospice Carementioning
confidence: 99%
“…However, as our systematic review of studies published between 2000 and 2010 on antimicrobial use in hospice and palliative care settings concluded there are limited data on the effectiveness of antimicrobial therapy to improve symptoms. [14] The strongest data suggest that antimicrobial therapy is most effective among patients with UTIs. [9,13,15] However, we also concluded that the methods used to assess symptom burden varied between studies and often deferred to subjective clinical assessment of improvement, sometimes supplemented with patient and caregiver assessment rather than validated measures.…”
Section: Safety and Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of antibiotics is also common in hospice care with a national study suggesting that approximately 27% of U.S. hospice patients received antibiotics in the final week of life (5). However, there is limited evidence that antibiotic use benefits hospice patients by reducing symptom burden, prolonging survival, or improving quality of life (6,7). Additional concerns with antibiotic use in hospice care include potential medication side effects and adverse events, increased risk of subsequent opportunistic infections, and prolonging the dying process (6,8).…”
mentioning
confidence: 99%
“…However, there is limited evidence that antibiotic use benefits hospice patients by reducing symptom burden, prolonging survival, or improving quality of life (6,7). Additional concerns with antibiotic use in hospice care include potential medication side effects and adverse events, increased risk of subsequent opportunistic infections, and prolonging the dying process (6,8). Furthermore, antimicrobial therapy increases selective pressure for antimicrobial-resistant organisms.…”
mentioning
confidence: 99%